The experience of premature birth for fathers: the application of the Clinical Interview for Parents of High-Risk Infants (CLIP) to an Italian sample - Candelori, Carla; Trumello, Carmen; Babore, Alessandra; Keren, Miri; Romanelli, Roberta (Frontiers in Psychology, 2015)
Aims: The study explored fathers’ experience of premature birth during the hospitalization of their infants, analyzing levels of depressive and anxiety symptoms as compared with mothers. Moreover the Italian version of the Clinical Interview for Parents of High-Risk Infant (CLIP) was tested through Confirmatory Factor Analysis. Methods: Couples of parents (N = 64) of preterm infants (gestational age < 37 weeks) were administered a socio-demographic questionnaire, the Edinburgh Postnatal Depression Scale, the State-Trait Anxiety Inventory and the CLIP after the admission to the Neonatal Intensive Care Unit (NICU). Results: Significant levels of anxiety and depressive symptoms and high percentages of subjects above the corresponding risk thresholds were found among fathers and mothers with higher scores among the latters. Confirmatory Factor Analysis of the CLIP showed an adequate structure, with better fit for mothers than for fathers. Conclusions: Results highlighted the importance for nurses and clinicians working in the NICU to consider not only the maternal difficulties but also the paternal ones, even if these are often more hidden and silent. In addition the CLIP may be considered an useful interview for research and clinical purposes to be used with parents of high-risk infants.